Peran Orang Tua dalam Membangun Kepercayaan Diri Pada Anak Usia Dini (THUFULA, 2014)
Golden age on the development of pre-school age should be a serious concern among the primary educators (parents). It is the simple period of building child’s personality. As a major figure, the parents play a role in shaping the personality of the child to be confident or insecure. This article tries to convince that the personality confident that a child will become a successful person